Rochester Cathedral, 604-1540 : an architectural history - McAleer, J. Philip (John Philip), 1935- (University of Toronto Press, 1999)
The aim of this study is to provide an architectural history of the medieval fabric of Rochester Cathedral, from its Saxon origins to the time of the dissolution of the monasteries by Henry VIII.